Multi-directional T-EMSD-based p-y model for recent loading history effects on lateral response of short pile and caisson in undrained clays. (1st January 2023) - Huang, Maosong; Cui, He; Shi, Zhenhao; Shen, Kanmin; Wang, Bin
Abstract: Rigid foundations supporting offshore wind turbines (OWT) like short piles and caissons can sustain multi-directional lateral loading. Moreover, the monotonic and cyclic response of these foundations can be affected by recent loading history aligned along directions different from the present one. To represent such recent loading history effects, a multi-directional p-y model is proposed for rigid foundations in undrained clays. The model is constructed by extending the uni-directional p - y model previously proposed by the authors based on Total-displacement-loading Extended Mobilisable Strength Design (T-EMSD) approach, and thus considering site-specific soil stress-strain relations and foundation geometries. The crux of the extension is to combine bounding surface plasticity and radial mapping with a moving projection center. The former effectively couples p - y response along orthogonal directions, while the latter is crucial for representing the influences of loading direction reversal and recent loading history effects. The proposed p - y model is evaluated against existing centrifuge tests and finite element analysis (FEA) of this work. Lastly, the proposed p - y model and FEA are used in parallel to highlight the effects of loading path rotation on monotonic and cyclic accumulative foundation response. These comparative analyses indicate that the proposed p-y model can reasonably represent recent loading history effects. Highlights: Multi-directional p-y model is proposed for recent loading history effect. Loading path rotation on monotonic and cyclic response of OWT foundation is studied. p - y model captures recent loading history effect from centrifuge tests and FEA.